LEGAL PROTECTION OF UIGHUR MUSLIM ETHNICS IN CHINA FROM PERSPECTIVE HUMAN RIGHTS - Endah Rantau Itasari (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2021)
Legal protection of ethnic Uighurs in Xinjiang, China in the perspective of Human Rights and to find out and study the resolution of cases of gross international human rights violations against ethnic Uighurs in Xinjiang, China. Legal protection of ethnic Uighurs based on Article 3,4,5,9,10,11, Universal Declaration of Human Rights by providing protection in the form of protection of the right to life, rights to freedom, and the right to self-security, etc. which is regulated in international legal instruments. 2) gross human rights violations committed by the Xinjiang government, China are not justified by international law because they violate the provisions stipulated in the subsequent Universal Declaration of Human Rights for incidents of human rights violations, then the dispute resolution between the two parties is carried out by negotiation or mediation first first If this method is not effective, the UN Security Council can submit the case to an international court such as the International Criminal Court set out in article 1 of the 1998 Rome Statute